INLAND FISHING GEAR AND FISHING TECHNIQUES OF INDIA - REMESAN, M. P.; PRAVIN, P.; MEENAKUMARI, B. (Journal of the Inland Fisheries Society of India, 2021)
Unscientific exploitation using nonselective fishing gear, destructive fishing methods and habitat degradation are cited as reasons for declining the fishery resources. Increasing the capture fish production of open water bodies require certain management practices and specialized skills. Lack of proper database on various fishing techniques, in the inland sector, is a hurdle for the managers and policy makers. This review documented all the available information related to inland fishing gear and fishing methods in India. Key words: Inland fishing gear, fishing methods, capture fisheries